Enhancing Design Thinking through Artificial Intelligence (AI)-Augmented Curriculum to Support Sustainable Development Goals (SDGs) in Chinese Vocational Education: A Bibliometric and Mixed-Methods Study - Feng Yang; Jiraporn Chano; Bahtiar Mohamad (Bumi Publikasi Nusantara, 2026)
Traditional vocational art and design education in China often emphasizes technical skills while providing limited support for creative problem-solving. This study developed and evaluated an artificial intelligence (AI)-augmented curriculum to enhance design thinking and support Sustainable Development Goals in Chinese vocational education. A bibliometric and mixed-methods design was applied through curriculum mapping, pre-test and post-test measurement, and semi-structured interviews. The findings showed improvement in overall design thinking, especially collaboration, problem orientation, and test iteration. However, empathy developed more slowly because generative AI produced standardized outputs with limited emotional depth. The study highlights the value of integrating AI with human guidance, reflective practice, and ethical creative judgment.